1968
DOI: 10.1161/01.cir.38.5s7.vii-1
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Adaptive Changes in Oxygen Transport and Body Composition

Abstract: The effects of a 20-day period of bed rest followed by a 55-day period of physical training were studied in five male subjects, aged 19 to 21. Three of the subjects had previously been sedentary, and two of them had been physically active. The studies after bed rest and after physical training were both compared with the initial control studies. Effects of Bed Rest All five subjects responded quite similarly to the bed rest period. The total body weight remained constant; however, lean body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
0
3

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 0 publications
12
108
0
3
Order By: Relevance
“…Many other investigators (21,24,119,120,287,309,345) have reported similar results. Stroke volume decreases in the upright position by about 33%.…”
Section: Cardiac Outputsupporting
confidence: 55%
See 2 more Smart Citations
“…Many other investigators (21,24,119,120,287,309,345) have reported similar results. Stroke volume decreases in the upright position by about 33%.…”
Section: Cardiac Outputsupporting
confidence: 55%
“…The process is progressive, and the rate tends to accelerate (74,77,287). The calcium loss appears to be more severe during weightlessness than during bed rest.…”
Section: R+10+17mentioning
confidence: 99%
See 1 more Smart Citation
“…The inactive life of the lower activity group led to a decrease in circulatory function, which in turn resulted in a higher heart rate than those observed for the other groups, both at rest and during similar activities. This speculation is supported by several early bed rest studies (19)(20)(21), in which it was reported that heart rate at rest and during submaximal exercise increases significantly after a prolonged period in a nonactive state, as represented by the bedridden state. For example, in 1948 Deitrick et al (19) reported that the resting pulse rate while lying in bed increases by 3.8 beats/minute after 6-7 weeks of bed rest, and in 1949 Tailor et al (20) reported that the pulse in a vertically tilted position (65 degrees) increases by 38 beats/ minute after 3 weeks of bed rest.…”
Section: Discussionmentioning
confidence: 75%
“…For example, in 1948 Deitrick et al (19) reported that the resting pulse rate while lying in bed increases by 3.8 beats/minute after 6-7 weeks of bed rest, and in 1949 Tailor et al (20) reported that the pulse in a vertically tilted position (65 degrees) increases by 38 beats/ minute after 3 weeks of bed rest. In 1968, Saltin et al (21) demonstrated that the increase in heart rate at rest and during submaximal exercise after a prolonged bed rest compensates for a decrease in stroke volume, and that the oxygentransporting ability at rest and during submaximal exercise is maintained by this system.…”
Section: Discussionmentioning
confidence: 99%